Overview of Blood Transfusion System of Iran: 2002-2011 - AM Cheraghali (Tehran University of Medical Sciences, 2012)
Despite importance of blood transfusion services as life saving procedures, some countries are unable to meet their national requirements for blood and blood components in a timely manner. Since establishment of Iran Blood Transfusion Organization (IBTO) in 1974 as an integral part of national health system, Iran has experienced a drastic improvement both in availability and safety of blood and blood products. Iran now has not only reached to a 100% non remunerated voluntary blood donation but also secured a national self sufficiency of blood and blood components. Efforts of IBTO as the sole player of transfusion medicines in Iran enabled the country for timely providing of life saving blood transfusion services for all Iranian patients in need of such services. In order to meet the country's demand in 2011 about 2 million units of whole blood for a population of about 75 million collected by IBTO. This indicates 26.2 donations per 1000 population. Currently about 94% of blood donors in Iran are 25-35 years old males and contribution of female donors in blood donation is less than 6%. IBTO screen all donated blood for important transfusion transmissible infections such as HBV, HIV, HCV and syphilis. Prevalence of HBsAg, HCV and HIV in donated blood in IBTO in 2011 was 0.20%, 0.06% and 0.004% respectively.